STUDI TENTANG POTENSI POHON KENARI (Canarium indicum) DI NEGERI MORELLA KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Umi Fahira Latukau; Miranda H. Hadijah; Hendrik S. E. S. Aponno (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
This study aims to examine the potential and ecological dominance of kenari (Canarium indicum) in Morella Village and to analyze the environmental factors influencing its growth. The research employed a vegetation analysis method using 25 plots measuring 20 × 20 m. Parameters observed included density, frequency, dominance, and Importance Value Index (IVI), along with measurements of soil pH, air temperature, humidity, and light intensity. The results show that C. indicum is the most dominant species with an IVI of 169.43, significantly higher than nutmeg (48.79) and clove (33.35). This indicates the strong ecological role of kenari as a key species within the local vegetation structure. Environmental conditions such as slightly acidic to neutral soil pH, temperatures of 27–28 °C, and high humidity support its growth. The presence of individuals across various growth stages reflects a stable regeneration pattern. The study concludes that kenari has high ecological and economic potential in Morella Village. Community-based management through agroforestry and consistent environmental monitoring are recommended to support sustainable productivity and ecosystem conservation.